Biodistribution of Mesenchymal Stem Cell-Derived Extracellular Vesicles in a Radiation Injury Bone Marrow Murine Model - Wen, Sicheng (Int J Mol Sci, 2019)
We have previously shown that injury induced by irradiation to murine marrow can be partially or completely reversed by exposure to human or murine mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs). Investigation of the biodistribution of EVs in vivo is essential for understanding EV biology. In this study, we evaluated the DiD lipid dye labeled MSC-EV biodistribution in mice under different conditions, including different MSC-EV doses and injection schedules, time post MSC-EV injection, and doses of radiation. DiD-labeled MSC-EVs appeared highest in the liver and spleen; lower in bone marrow of the tibia, femur, and spine; and were undetectable in the heart, kidney and lung, while a predominant EV accumulation was detected in the lung of mice infused with human lung fibroblast cell derived EVs. There was significantly increased MSC-EV accumulation in the spleen and bone marrow (tibia and femur) post radiation appearing with an increase of MSC-EV uptake by CD11b+ and F4/80+ cells, but not by B220 cells, compared to those organs from non-irradiated mice. We further demonstrated that increasing levels of irradiation caused a selective increase in vesicle homing to marrow. This accumulation of MSC-EVs at the site of injured bone marrow could be detected as early as 1 h after MSC- EV injection and was not significantly different between 2 and 24 h post MSC-EV injection. Our study indicates that irradiation damage to hematopoietic tissue in the spleen and marrow targets MSC-EVs to these tissues.